(untitled) (International Journal of Environmental Sciences, 2025)
Aim: To assess gender-based variations in primary canines and intercanine width among Indian children using odontometric measurements, aiding forensic and anthropological research. Materials and Methods: A cross-sectional study was carried out using a digital Vernier calliper to measure 258 sets of maxillary and mandibular diagnostic dental casts, with a single examiner ensuring consistency. Measurements recorded included Mesiodistal width (MD), Cervico incisal height (CI), Labiolingual/Buccopalatal width (LL/BP), and Intercanine width (ICW) of the maxillary and the mandibular canines. Statistical analysis was done using SPSS (version 20.0). Results: The mean linear dimensions of the primary canine with respect to MD, CI and LL/BP was higher in males as compared to females whereas females exhibited greater mandibular ICW. Significant differences were noted in MD width of 83, LL/BP widths and mandibular intercanine width, confirming sexual dimorphism. Conclusion: The study confirms sexual dimorphism in primary canines, supporting forensic and anthropological applications.